2019
DOI: 10.1038/s41598-019-43034-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topography and protecting barriers on revegetation of sandy land, Southern Tibetan Plateau

Abstract: Revegetation on sandy land has attracted worldwide attention, especially on the extremely fragile alpine eco-region of the Tibetan Plateau. However, the effectiveness of revegetation and its controlling factors have rarely been reported. We collected plant growths and species composition from seven field sites in 2011 and conducted a follow-up random investigation in 2016. The indicators, including richness and diversity, were used to compare the differences among these sites based on redundancy and cluster an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Sand dune habitats are changing by many factors e.g. dune encroachment, sand accumulation, and wind erosion [53].…”
Section: Discussionmentioning
confidence: 99%
“…Sand dune habitats are changing by many factors e.g. dune encroachment, sand accumulation, and wind erosion [53].…”
Section: Discussionmentioning
confidence: 99%
“…Natural restoration is an ecosystem management approach to reduce the adverse effects of unreasonable human activities, such as overgrazing, extensive land reclamation, and excessive firewood collection , Peng et al 2019. Artificial restoration mainly includes afforestation and revegetation of a seriously degraded land (Kang et al 2018, Liao et al 2019). Many scholars have initiated studies on ecological restoration to control the spread of aeolian desertification and restore degraded grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have explored the artificial restoration of ecosystems , screening of suitable plant species (Li et al 2019a), the effects of fencing enclosures on soil seed banks (Shang et al 2013), and the effects of micro-topography on revegetation (Li et al 2019a). Previous studies have shown that Artemisia sphaerocephala, Artemisia younghusbandii, and Heteropappus gouldii are suitable as the pioneer species for revegetation of a sandy land (Li et al 2019a, Liao et al 2019. Previous studies have shown that Artemisia sphaerocephala, Artemisia younghusbandii, and Heteropappus gouldii are suitable as the pioneer species for revegetation of a sandy land (Li et al 2019a, Liao et al 2019.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations